Professional cooking - Gisslen, Wayne (New Jersey : John Wiley & Son, Inc., 2007)
Presents step-by-step instructions for professional cooking techniques; covers cooking principles, sanitation and safety, nutrition, tools and equipment, and cost management; contains 1,200 recipes; and includes Wiley CulinarE-Companion software on a CD-ROM, providing all of the recipes from the book and the ability to modify them, create shopping lists, and perform other tasks.
The food service industry -- Sanitation and safety -- Tools and equipment -- Basic cooking principles -- Menus, recipes, and cost management -- Nutrition -- Mise en place -- Stocks and sauces -- Soups -- Understanding meats and game -- Cooking meats and game -- Understanding poultry and game birds -- Cooking poultry and game birds -- Understanding fish and shellfish -- Cooking fish and shellfish -- Understanding vegetables -- Cooking vegetables -- Potatoes -- Legumes, grains, pasta, and other starches -- Cooking for vegetarian diets -- Salads and salad dressings -- Sandwiches -- Hors d'oeuvres -- Breakfast preparation -- Dairy and beverages -- Sausages and cured foods -- Pates, terrines, and other cold foods -- Food presentation and garnish -- Bakeshop production : basic principles and ingredients -- Yeast products -- Quick breads -- Cakes and icings -- Cookies -- Pies and pastries -- Creams, custards, puddings, frozen desserts, and sauces.
Includes index.
Keywords: QUANTITY COOKERY